A rare case of intussusception through a prolapsed end colostomy. Issue 7 (19th July 2021) - Temperley, Hugo; Waters, Caitlin; Murray, Cian; Donlon, Noel E; Donohoe, Claire L
Abstract: Intussusception through a prolapsed end colostomy is amongst the rarest of stoma complications. In this case report, we discuss the therapeutic approach to this complication and provide an update of the existing literature. A 66-year-old male presented with a prolapsed colostomy that was ischaemic in appearance. Intraoperatively, a small bowel intussusception within the prolapsed colon was identified. A subtotal colectomy was subsequently performed to prevent further volvulus formation. When patients present with a prolapsing oedematous enterostomy that cannot be reduced, careful clinical examination is required. If there is vascular compromise, exploratory laparotomy is mandatory.